Hérondas et la rhétorique - Johann Goeken (Aitia, 2021)
The poet Herodas knows the theory and the practice of rhetoric. Mimes represent situations that can be interpreted according to the codes and procedures of rhetorical art. Oratorical aptitude, which serves the comic, is an essential quality for the poet and his audience.